An exploratory study on Situational Leadership practice of principals as perceived by the teachers at Pondok Modern Gontor Indonesia - Azani, Mohammad Zakki (Institute of Education, International Islamic University Malaysia, 2011)
A case-study approach is presented to demonstrate how the practices of Situational Leadership, a management theory developed by Hersey and Blanchard (2001), by school principals are able to make them more receptive to educational innovation in school programmes. Situational Leadership factors provide practical situational knowledge of school principals' leadership style to teachers as the object of the principals' programmes. Situational Leadership has several strengths particularly for practitioners and it provides a straightforward approach that is easily applied in a variety of settings including in educational leadership for shaping excellent school leadership and school achievement. The subjects of this study were 297 teachers from five Pondok of learning in Indonesia. The data obtained from this study were analyzed by using Exploratory Factor analysis and varimax rotation method to reduce unrelated factors and to identify if all items had been practiced by the principals. Besides that, factor analysis is also applied on both pilot and actual variables for reliability and validity to identify the underlying factors. Moreover, descriptive analysis methods show the demographic data of the respondents as well as one-way Anova and t-test analysis. Both methods are conducted to compare teachers' perception on the characteristics of Situational Leadership practiced by their principals. The respondents stated that they were aware that their principals used all four situational leadership styles in managing their staff. This means that the school principals had the ability to handle the teachers in a particular environment and they preferred using participative styles; some even went to considerable lengths to avoid delegating. The teachers combined administrative work with teaching to run all school activities to determine the developmental level of the individuals or groups in relation to a specific task that the leader was attempting to accomplish. Hence, the school principals were also willing to share ideas and provide opportunity for clarification before facilitating teachers in decision-making process. However, the construct of Situational Leadership readiness of the followers was questioned, and directions for further research into some of the hypotheses generated by this study are proposed.